Taurine Attenuates Disuse Muscle Atrophy Through Modulation of the xCT-GSH-GPX4 and AMPK-ACC-ACSL4 Pathways - Xi Liu; Yifen Chen; Linglin Zhang; Zhen Qi; Longhe Yang; Caihua Huang; Li Wang; Donghai Lin (Antioxidants)
Disused muscle atrophy (DMA) is characterized by skeletal muscle loss and functional decline due to prolonged inactivity. Though evidence remains limited, recent studies suggest that ferroptosis, an iron-dependent, lipid peroxidation-driven form of cell death, may contribute to DMA. Taurine, a natural amino acid enriched in energy drinks, can improve the proliferation and myogenic differentiation potential of myoblasts. This study aimed to investigate whether taurine supplementation could protect against DMA and explore its potential role in modulating ferroptosis. Using a hindlimb suspension-induced DMA model in male C57BL/6J mice (6–8 weeks old), we assessed muscle mass, function, ferroptosis-related markers, histopathological changes, and metabolic alterations. The results showed that taurine supplementation improved muscle strength and morphology while attenuating markers of ferroptosis, including iron accumulation, lipid peroxidation, and glutathione and related protein (NRF2, GPX4, and xCT) depletion. Metabolomic analysis suggested that taurine modulates disorders in glutathione and lipid metabolism, potentially associated with the regulation of the xCT-GSH-GPX4 and AMPK-ACC-ACSL4 pathways. While these findings support a protective role for taurine and a possible link between ferroptosis and DMA, further functional studies are needed to confirm causality and assess the compound’s translational potential. This study provides initial in vivo evidence implicating ferroptosis in DMA and highlights taurine as a promising candidate for future therapeutic exploration.